Management Information Systems: Planning, Evaluation and Implementation. - Stohr, Edward A.; Moriarty, Shane R. (The Accounting Review, 1990)
Abstract Reviews the book `Management Information Systems: Planning, Evaluation and Implementation,' edited by John S. Chandler and H. Peter Holzer.